ANGKRINGAN 5.0: IMPLEMENTASI GREEN ENERGY DAN KOMPUTASI CERDAS - Hasanah, Herliyani; Lestari, Wiji; Nugroho, Novemy Triyandari; Susanto, Rudi (Universitas Mataram, 2024)
Society 5.0 is a concept of convenience for humans controlled by technology in fulfilling social and economic behavior. The use of technology in the form of hardware and software requires high energy. The need for energy will add to problems in energy supply. To anticipate this, the equipment and facilities used by small and medium enterprises (SMES) must be designed to use sustainable energy and resources or green energy. The angkringan business is one of the typical SMES in Indonesia. The angkringan business also faces tough competition to survive in the culinary business. For this reason, innovation and development are needed, including strategies that carry traditional nuances combined with modern technological information. Green energy is developed using solar cells which will be implemented in Gerobak Angkringan. Intelligent computing will be implemented in applications to manage solar cell energy distribution and prediction. Furthermore, intelligent computing will be implemented in the Angkringan 5.0 application. The stages of implementing devotion activities include preparation, implementation and evaluation. The off-grid PLTS unit implemented for the Angkringan Suhe Railway Museum uses 200 Wp solar panels. An intelligent computing system has been implemented in the application to manage the distribution and prediction of solar cell energy. Furthermore, intelligent computing will be implemented in the Angkringan 5.0 application. This application is useful for helping small and medium enterprises (SMES), especially Angkringan traders. This application is useful for monitoring the weather when selling angkringan, so that angkringan traders anticipate these conditions. The System Usability Scale (SUS) Testing Instrument with 10 questions obtained a SUS test calculation result of 82.5, so it can be said that the system built meets the SUS.